Stability of 10 mg/mL cefuroxime solution for intracameral injection in commonly used polypropylene syringes and new ready-to-use cyclic olefin copolymer sterile vials using the LC-UV stability-indicating method. (2nd January 2016) - Feutry, Frédéric; Simon, Nicolas; Genay, Stéphanie; Lannoy, Damien; Barthélémy, Christine; Décaudin, Bertrand; Labalette, Pierre; Odou, Pascal
Abstract: Context : Injecting intracameral cefuroxime has been found beneficial in reducing the risk of postoperative endophthalmitis but its use has been limited through a lack of approved marketing and of ready-to-use single-units as well as the problem of aseptic compounding. Objective : Our aim was to assess a new automated primary packaging system which should ensure a higher level of sterility, thanks to its closed, sterile, ready-to-use polymer vial called "Crystal® vial". The chemical stability of a 10 mg/mL cefuroxime solution was compared in 1 mL Crystal® vials and 1 mL Luer-lock polypropylene syringes (actual reference) to eliminate any potential and specific interactions with its cyclic olefin copolymer (COC) body and elastomer stopper. Methods : Cefuroxime solution was introduced into vials and syringes and stored at −20 °C, +5 °C and +25°C/60% Relative Humidity. Cefuroxime concentration and the relative amount of the main degradation product (descarbamoyl-cefuroxime) were both determined by an HPLC/UV method indicating stability. Solutions were considered steady if the concentration remained at over 90% of the initial value. In the adapted storage conditions, the evolution of osmolality, pH and sterility was assessed. Results : Stability profiles were identical between vials and syringes in all storage and temperature conditions. The solution was stable (cefuroxime concentration, pH and osmolality) and still sterile for 365 days at −20°C. The concentration fell below 90% after 21 days at +5 °C and after 16 h at +25°C/60%s relative humidity. Conclusions : The COC and thermoplastic elastomer of the vials had no impact on the degradation process confirming its possible use for a ready-to-use cefuroxime solution single-unit dose.